An investigation on chemical bubble column using ultrasonic tomography for imaging of gas proﬁles - Rahiman, M.H.F.; Rahim, R.A.; Rahim, H.A.; Mohamad, E.J.; Zakaria, Z.; Muji, S.Z.M. (Elsevier Science Ltd, 2014)
In this paper, we carried out a tomographic investigation of a chemical bubble column using ultrasonic sensor. The ultrasonic tomography sensing array was constructed to operate in transceiver-mode and was clamped on the exterior circumference of the column. The time-of-ﬂight and arrival-time analysis was studied to obtain the signal information. Some experiments were carried out using known static proﬁles and were compared with the actual proﬁles. The ﬁndings showed promising results where the sensing array could detect gas bubble proﬁles down to 3 mm in diameter, and the conclusions were made at the end of the paper.